Nurses’ readiness in research utilization: Moving toward - Mehrdad, Dr Neda; Salsali, Dr Mahvash; Kazemnejad, Dr Anoshirvan (Advances in Nursing & Midwifery, 2011)
Nurses’ readiness in research utilization: Moving toward evidence-based practice Mehrdad, N.1* (PhD); Salsali, M.2 (PhD); Kazemnejad, A.3 (PhD) 1. Assistant Professor, Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Iran University of Medical Sciences, Tehran, Iran. *(Corresponding Author) e-mail: neda@iums.ac.ir 2. Professor, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran. 3. Professor, Dept. of Biostatistics, Tarbiat Modarress University, Tehran, Iran. Abstract Background and aim Research utilization is a mechanism for transferring the results of research into practice and improving the quality of care in nursing. The aim of this study was to determine nurses’ readiness to utilize research needed for applying evidence-based practice. Materials and methods In this descriptive study, 375 nurses in all teaching hospitals affiliated with Tehran University of Medical Sciences were selected by stratified random sampling method. A 4-part questionnaire with open and close-ended questions including professional profile, research activities, research skills and access to research resources was used foe data collection. Content as well as face validities and Cronbach’s α for reliability (0.82) were identified. Findings 85.9% of nurses had weak readiness in research utilization. Both research activities and skills were also low (71.4% and 82.7% respectively). 44% of nurses had insufficient access to research resources. A significant relationship was found between nurses’ educational level, participation in research activities as well as English language skills and their readiness in research utilization. Conclusion Lack of skills and inaccessibility to research findings lead to weak readiness for research utilization. With respect to the importance of utilizing research findings, organizational and administrative support, continuing education programs, well-defined processes and pathways to facilitate research utilization need to be provided for nurses. Keywords: Research utilization, Evidence-based practice, Nurses. *Corresponding Author: Neda Mehrdad. Assistant Professor, Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Iran University of Medical Sciences, Tehran, Iran. E-mail: neda@iums.ac.ir <span style="font-size: 16pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-language: FA; mso-bidi-font-family: ’B Nazanin’; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">Effects of bladder irrigation with chlo